1986
DOI: 10.1037/0033-2909.100.3.364
|View full text |Cite
|
Sign up to set email alerts
|

Television violence and aggression: The debate continues.

Abstract: Many social scientists believe there is a causal relation between viewing television violence and aggression. That majority consensus has recently been challenged on the grounds that the data are inconsistent, that different methods of study may be subject to systematic biases, and that the findings have limited generalizability to real-world violence. In this review we reply to these challenges. We conclude that the data support a bidirectional causal relation between viewing television violence and aggressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0
1

Year Published

1987
1987
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(28 citation statements)
references
References 33 publications
1
26
0
1
Order By: Relevance
“…For example, a large body of research has converged on findings that viewing television violence affects both short-term and longterm aggressive behavior. [33][34][35] Along these lines, our results suggest that the AAP was right to be concerned that time spent viewing would be negatively related to the time that children spend interacting with their parents. We found a consistent pattern of fairly large negative relationships among television viewing and time spent interacting with both parents and siblings.…”
Section: Discussionsupporting
confidence: 55%
“…For example, a large body of research has converged on findings that viewing television violence affects both short-term and longterm aggressive behavior. [33][34][35] Along these lines, our results suggest that the AAP was right to be concerned that time spent viewing would be negatively related to the time that children spend interacting with their parents. We found a consistent pattern of fairly large negative relationships among television viewing and time spent interacting with both parents and siblings.…”
Section: Discussionsupporting
confidence: 55%
“…For example, Berkowitz and Rawlings (1963) showed that violent movie scenes led to justification of personal aggressive behavior. Experimental studies have been criticized for their somewhat artificial nature, but field experiments have produced similar results in more realistic settings (Friedrich & Stein, 1973;Leyens, Camino, Parke, & Berkowitz, 1975;Friedrich-Cofer & Huston, 1986). However, it is not so much the immediate effects of media violence exposure that are of concern, but rather the aggregated long-term effects.…”
Section: Movie Ratingsmentioning
confidence: 85%
“…Today, evidence has been collected from many more lab experiments, some field experiments, and a number of surveys (Comstock & Paik, 1987). Although there are a few critics who disagree (e.g., Freedman, 1984), most reviews of the research conclude that heavy exposure to media violence increases the degree to which children will engage in aggressive behavior (see Andison, 1977;Friedrich-Cofer & Huston, 1986). Moreover, these effects are not limited to childhood.…”
Section: The Effects Of Violent Contentmentioning
confidence: 94%